2007
DOI: 10.1093/humrep/dem360
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reproductive outcomes in urban women with adeno-associated virus-2 infections in early pregnancy

Abstract: Primary or reactivated AAV-2 infection (maternal IgM seropositivity) early in pregnancy was associated with adverse reproductive outcomes associated with placental dysfunction, including pre-eclampsia, stillbirth and spontaneous preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 30 publications
1
34
1
2
Order By: Relevance
“…These changes in trophoblast function could explain why both HSV-1 and HSV-2 have been associated with spontaneous pregnancy loss (89) and IUGR pregnancies (82,84). AAV2 also induces trophoblast apoptosis and reduces cell invasion (18,90,91) and is associated with spontaneous miscarriage, stillbirth (92), and preeclampsia (82,91,93). Collectively, these results demonstrate that viral infection of the trophoblast can alter placental function and could result in suboptimal conditions for fetal growth and development.…”
Section: Viral Infections and Early Placental Developmentmentioning
confidence: 92%
“…These changes in trophoblast function could explain why both HSV-1 and HSV-2 have been associated with spontaneous pregnancy loss (89) and IUGR pregnancies (82,84). AAV2 also induces trophoblast apoptosis and reduces cell invasion (18,90,91) and is associated with spontaneous miscarriage, stillbirth (92), and preeclampsia (82,91,93). Collectively, these results demonstrate that viral infection of the trophoblast can alter placental function and could result in suboptimal conditions for fetal growth and development.…”
Section: Viral Infections and Early Placental Developmentmentioning
confidence: 92%
“…Clinical studies have shown a strong association between intrauterine bacterial or viral infections and pregnancy complications such as abortion, preterm labor, intrauterine growth restriction, and preeclampsia [1][2][3]. During intrauterine infection, the placenta represents a mechanical and immunological barrier whose innate immune competences are essential to restrict infection progress.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have associated this infection with other adverse problems and reproductive outcomes such as male infertility, trophoblastic gestational disease, premature amniorrexis, preterm deliveries, and preeclampsia [Burguete et al, 1999;Erles et al, 2001;Arechavaleta-Velasco et al, 2008]. However, the association with human disease is controversial, such as the role of AAV in human abortion [Friedman-Einat et al, 1997;Matovina et al, 2004].…”
Section: Discussionmentioning
confidence: 99%